Design of β-CD–surfactant complex-coated liquid crystal droplets for the detection of cholic acid via competitive host–guest recognition1. Issue 43 (28th May 2015) - Deng, Jinan; Lu, Xiaoyan; Constant, Colin; Dogariu, Aristide; Fang, Jiyu
<x xml:space="preserve">Abstract</x> We report the use of β-CD–C14TAB complex-coated 5CB droplets for the selective detection of cholic acid, in which the β-CD–C14TAB complex at the surface of the 5CB droplets is used as a selective barricade and the configuration transition of the 5CB inside the droplets serves as an optical probe.